Selection of agility tests according to sports branches in terms of basic motor characteristics - Ucan, I. (African Educational Research Journal, 2020)
The aim of this study is to determine the most usable of the three most commonly used tests for male and female athletes, which are applied to determine the agility levels of athletes according to sports branches in terms of their basic motor characteristics. The research group consists of a total of 72 volunteer students, 26 females and 46 males, who were studying at the Coaching Department at Bayburt University School of Physical Education and Sports. In the study, the Sit and Reach test, Takkei brand back and leg dynamometer, 20-meter speed test, T-test which is one of the agility tests, the 505 test and Illinois tests were used. In the analysis of the data obtained in the study, descriptive statistics and normality analysis were performed by SPSS 25.0 program. In order to determine the relationship between motoric properties and agility test values Bivariate-Pearson Correlation test was applied. 0.05 was determined as the level of significance. In the study, a negative correlation was found between women`s leg strength and T-test, and flexibility values and the 505 test, while a positive correlation was found between the speed values and the Illinois test. And statistically significant and positive correlations were found between men`s leg strength and Illinois test, and speed values and T-test. In addition, a negative relationship was found between Illinois test and flexibility values although it is not significant. The study showed that while agility test is preferred; T-test should be preferred for branches requiring strength, Illinois test should be preferred for branches requiring speed and 505 test for branches requiring flexibility in women. For men, T-test should be preferred in branches that require speed, and Illinois test should be preferred in branches that require flexibility. In addition, it shows that the Illinois test should not be preferred in the branches requiring force.